Dry ginger and Schisandra chinensis modulate intestinal flora and bile acid metabolism to treatment asthma - Yu, Yantong; Geng, Shuang; Bu, Chao; Cao, Gang; Han, Yanquan; Xie, Dongmei; Hong, Yan (Frontiers in Microbiology, 2025)
Background and aimsZingiber officinale Rosc (Dry ginger) and Schisandra chinensis (Turcz.) Baill (Schisandra chinensis) drug pairs (DSP) are often used as drug pairs for the treatment of asthma, and these two traditional Chinese medicines (TCM) are also the core components of multiple TCM. However, its specific pharmacological mechanism needs further research. The aim of this study is to investigate the effects of DSP on intestinal flora and bile acid metabolism in rats with asthma caused by cold, and to provide experimental evidence for its clinical application.Materials and methodsSixty male rats are divided into five groups, 12 rats per group. Except for control groups, other groups of rats use the method of “abdominal injection of “OVA + ice water swimming” to establish cold cough rats models. After the administration cycle is over, an optical microscope count method is used to detect eosinophils (EOS) and neutrophils (Neu) in bronchoalveolar lavage fluid (BALF); Enzyme-Linked Immunosorbent Assay (ELISA) method detects Immunoglobulin E (IgE), Interleukin-13 (IL-13), Interleukin-4 (IL-4), Tumor Necrosis Factor-α (TNF-α), Interferon-γ (INF-γ); Western Blot (WB) and Reverse Transcription-Polymerase Chain Reaction (RT-PCR) analysis was used to detect Forkhead box protein P3 (Foxp3) and Transforming Growth Factor-beta 1 (TGF-β1) proteins expression. In addition, Using 16S rDNA sequencing reveal the role of intestinal flora in asthma and the effect on the gut microbiome after DSP treatment. We also examined Farnesoid X Receptor (FXR) proteins expression, and finally used ultra performance UPLC-MS/MS to analyze bile acids (BAs) contentin in rats.ResultsDSP inhibits asthma inflammation. It alleviates inflammatory factors, suppresses the inflammatory response in asthmatic rats by regulating FOXP3 and TGF-β1 in Treg cells, and reduces tissue damage. After DSP treatment, intestinal flora changed: harmful bacteria like Streptococcus decreased, while beneficial bacteria such as Candidatus - Arthromitus and Ligilactobacillus increased. These changes can be potential markers for DSP-intervened asthma. Also, DSP increased FXR protein expression and changed the bile acid spectrum: Deoxycholic acid (DCA) increased, allocholic acid (ACA), glycolithocholic acid (GLCA), glycochenodeoxycholic acid (GCDCA) andglycoursodeoxycholic acid (GUDCA) decreased.ConclusionThis study has preliminarily revealed that DSP has the effect of alleviating inflammation levels, also regulate the expression of FOXP3 and TGF-β1 proteins, and has an impact on the gut microbiota and bile acid metabolism, thereby exerting an improving effect on asthma and providing a reference for the clinical application of traditional Chinese medicine in the treatment of asthma.